2011
DOI: 10.7763/ijesd.2011.v2.131
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop Analysis of Square and Hexagonal Cellsand its Effects on the Performance of Catalytic Converters

Abstract: Stringent emission regulations around the world necessitate the use of high-efficiency catalytic converters in vehicle exhaust systems. Therefore, determining the optimum geometry of the honeycomb monolith structure is necessary. This structure requires a high surface area for treating gases while maintaining a low pressure drop in the engine. In the present paper, an adapted sub-grid scale modeling is used to predict the pressure loss of square-and hexagonal-cell-shaped honeycomb monoliths. This sub-grid scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The model predicts the minimum pressure drop for the lowest flow rate (0.4 kg/h) as 41 Pa with a linear increase of the pressure drop with the increase in the mass flow rate, resulting in pressure drop of 117 Pa at the highest examined flow rate (1.1 kg/ h). Similar trend, where the pressure drop shows a linear dependency to the mass flow rate, is found in the literature [47,57]. It can be concluded that the CFD prediction results for pressure drop agree well with experimentally measured pressure drops.…”
Section: Model Validationsupporting
confidence: 88%
See 3 more Smart Citations
“…The model predicts the minimum pressure drop for the lowest flow rate (0.4 kg/h) as 41 Pa with a linear increase of the pressure drop with the increase in the mass flow rate, resulting in pressure drop of 117 Pa at the highest examined flow rate (1.1 kg/ h). Similar trend, where the pressure drop shows a linear dependency to the mass flow rate, is found in the literature [47,57]. It can be concluded that the CFD prediction results for pressure drop agree well with experimentally measured pressure drops.…”
Section: Model Validationsupporting
confidence: 88%
“…13. In the mass flow rate range of interest, the pressure drop of the honeycomb varies linearly with the mass flow rate [47,56,62]. Considering the flow in the honeycomb channels is fully laminar, the viscous effects are the main contributor to the pressure drop in the studied mass flow rate range [60].…”
Section: Pressure Dropmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow uniformity was increased by utilizing higher cell density monoliths with smaller hydraulic diameter and by splitting the monolith into two parts separated by a gap [8][9][10][11]. Lower flow uniformity was observed in 3D steady state and transient numerical simulations in systems with higher monolith-to-inlet diameter ratios [12,13].…”
Section: Introductionmentioning
confidence: 99%